Perlindungan terhadap Ibu Pengganti (Surrogate Mother) dalam Prespektif Hukum Hak Asasi Manusia di Indonesia - Qintarawati, Alifia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research aims to find out about the protection of human rights and international human rights regarding the practice of Surrogate Mother and to find evidence that there are no legal provisions that can protect the human rights of all parties involved in this practice. This type of research is normative legal research. Through a legislative approach that applies in Indonesia. The results of this research show that the practice of renting a womb violates human rights. The practice of surrogacy or womb renting cannot be implemented in Indonesia because it is considered to violate the human rights of mothers who rent out their wombs to have offspring from a valid marriage in accordance with article 28 paragraph (1) of the 1945 Constitution. Apart from that, when an agreement is made, the agreement is not recognized or considered invalid because a woman's womb is not an object of an agreement. Apart from that, the unclear status of the children born can cause defects if inbreeding occurs. These legal findings show that there are no clear legal provisions that can protect the human rights of all parties involved, including children born as a result of this practice. The legality of renting a womb in international human rights helps married couples to have children. As a form of absolute right as a human right which is also regulated in international instruments including the UDHR and CEDAW. This research aims to find out about the protection of human rights and international human rights regarding the practice of Surrogate Mother and to find evidence that there are no legal provisions that can protect the human rights of all parties involved in this practice. This type of research is normative legal research. Through a legislative approach that applies in Indonesia. The results of this research show that the practice of renting a womb violates human rights. The practice of surrogacy or womb renting cannot be implemented in Indonesia because it is considered to violate the human rights of mothers who rent out their wombs to have offspring from a valid marriage in accordance with article 28 paragraph (1) of the 1945 Constitution. Apart from that, when an agreement is made, the agreement is not recognized or considered invalid because a woman's womb is not an object of an agreement. Apart from that, the unclear status of the children born can cause defects if inbreeding occurs. These legal findings show that there are no clear legal provisions that can protect the human rights of all parties involved, including children born as a result of this practice. The legality of renting a womb in international human rights helps married couples to have children. As a form of absolute right as a human right which is also regulated in international instruments including the UDHR and CEDAW.